Consumer expectation and perception of fast food outlets : an empirical study in Kota Bharu, Malaysia - Naila Aaijaz; Mohamed Dahlan Ibrahim; Ghazali Ahmad (International Association of Computer Science and Information Technology : Singapore, 2009)
Objective - Using the data from a consumer survey, this study aims to investigate the relationship between consumers's fast food outlet loyalty (in years) and the attitude of young consumers living in Kota Bharu city. The study also investigates the importance of quality of the product that are offered to the customer. It also studies the importance of facilty location and layout which bring convenience to the customer and increase efficiency at the outlets. One step futher we also walkthrough the service delivery process and service package offered when dealing with customers by fast food outlests. Design/Methodology/Approach - This study was conducted via undergraduate business course students of University Malaysia Kelantan (UMK) who as young customers filled a self-administered brief questionnaire on their visits to various fast food outlets in Kota Bharu, Kelantan State Malaysia. Findings - The results indicate that food quality, overall cleanliness of the oulet, services efficiency and facility layout provided by the outlet influences the fast food brand loyalty of young customers, Purchaces were mainly due to the four factors - perception of customers on food quality, cleanliness, facility layout, efficiency in service delivery.